2022
DOI: 10.1111/acem.14490
|View full text |Cite
|
Sign up to set email alerts
|

In their own words: Experiences of emergency health care workers during the COVID‐19 pandemic

Abstract: Background During the COVID‐19 pandemic, a substantial number of emergency HCWs have screened positive for anxiety, depression, risk of post‐traumatic stress disorder and burnout. The purpose of this qualitative study is to describe the impact of COVID‐19 on emergency care providers’ health and well‐being using personal perspectives. We conducted in‐depth interviews with emergency medicine (EM) physicians, EM nurses and emergency medical service providers at ten collaborating sites across the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…Kuwahara et al suggest change at the level of the preparedness phase (of disaster/emergency/crisis management), including "multiple plans and measures to maintain social ties should be prepared at the individual level (e.g., family, friends, neighborhood), organizational or community levels, and societal levels to prevent or mitigate the negative impact of social isolation and its related problems. 37 " Finally, shortages of PPE were a prominent issue early in the pandemic 5,28,38 ; adequate PPE is an essential component to healthcare worker wellness in this crisis. 39,40 PPE has no longer become a critical issue for the majority of US hospitals, but the variation in hospital leadership's ability to address the health and safety of frontline workers affected morale and had downstream effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuwahara et al suggest change at the level of the preparedness phase (of disaster/emergency/crisis management), including "multiple plans and measures to maintain social ties should be prepared at the individual level (e.g., family, friends, neighborhood), organizational or community levels, and societal levels to prevent or mitigate the negative impact of social isolation and its related problems. 37 " Finally, shortages of PPE were a prominent issue early in the pandemic 5,28,38 ; adequate PPE is an essential component to healthcare worker wellness in this crisis. 39,40 PPE has no longer become a critical issue for the majority of US hospitals, but the variation in hospital leadership's ability to address the health and safety of frontline workers affected morale and had downstream effects.…”
Section: Discussionmentioning
confidence: 99%
“…23 Failure to implement existing crisis care standards, when indicated, caused unnecessary moral distress. 5,29,30 Moral distress can affect everyone; it has been suggested that it be openly discussed given that it is a healthy, rather than a pathological, response. 41 Moral distress can be mitigated by systemic factors despite similar clinical exposures 42 ; this highlights the power of systemic decisions to minimize moral distress in addition to addressing it through individual physician wellness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent survey, emergency medicine has shifted to become the specialty with the highest degree of burnout [13]. Many healthcare leaders attribute such a high rate to the working conditions and risks of the COVID-19 pandemic [14][15][16], which has undoubtedly also impacted the experience and wellness of trainees. This sustainable retreat program has demonstrated success with resident satisfaction and is the first report in the literature for emergency medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The verbatim answers to each of these open-ended queries were assessed in a completely blinded manner vis-à-vis the quantitative data. The authors independently evaluated these answers using qualitative content analysis [44][45][46] and subsequently discussed the assessments until concordance was attained.…”
Section: Qualitative Data: Open-ended Queries In the Self-administere...mentioning
confidence: 99%